Eosinophilic Pustular Folliculitis Mimicking Varicella: A Diagnostic Challenge in an Adolescent Patient - Farisa Mutahallia; Triasari Oktavriana; Novan Adi Setyawan; Aizawanda Rizqi Eiffellia; Arista Kautsar Rahman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Eosinophilic pustular folliculitis (EPF), or Ofuji disease, is a rare non-infectious inflammatory dermatosis typically affecting middle-aged adults. Its clinical resemblance to infectious exanthems often leads to significant diagnostic delays, particularly in atypical age groups. Case presentation: A 15-year-old male presented with a one-month history of progressive erythematous papules, pustules, and crusted erosions distributed across the face, trunk, and extremities. The patient was initially misdiagnosed with varicella and treated with acyclovir without clinical response. Physical examination and Gram staining ruled out primary bacterial infections. Laboratory investigations revealed significant peripheral eosinophilia (12.3%). A 5-mm punch biopsy confirmed the diagnosis, showing dense eosinophilic and neutrophilic infiltration of the hair follicles and peri-adnexal structures. Management with systemic and topical corticosteroids led to rapid resolution of lesions and normalization of eosinophil levels. Conclusion: This case underscores the necessity of considering EPF in the differential diagnosis of persistent papulopustular eruptions in adolescents. Early histopathological intervention is critical to prevent unnecessary antimicrobial therapy and ensure targeted anti-inflammatory treatment.